Increasing farmer skills processing animal feed using fermentation methods to increase nutrition for livestock - Bagus Nuari Priambudi; Turrini Yudiarti; Sri Sumarsih; Lilik Krismiyanto (University of Merdeka Malang, 2025)
Feed is one of the things that really determines the success of a livestock business. In the rainy season, quality feed ingredients are difficult to obtain. This has the effect that farmers have a look alternative feed so that livestock feed needs can be met properly. One method that can be used to maintain the nutritional content of alternative feed is the fermentation process. This community service activity is part of the collaboration between the Pekalongan Regency Government and Diponegoro University. This activity will be carried out from June to December 2023 with service partners from the Tanjungkulon Village Livestock Group Kajen District consisting of 15 - 20 participants. Implementation of activities is carried out using counseling, practice and mentoring methods for livestock groups. This activity is considered very useful for improving the skills of farmer groups. Because livestock groups can use ingredients that are sold generally to make higher quality animal feed. This was reinforced during the monitoring process with the success rate indicator for making animal feed reaching 75 – 80%. It is hoped in the future this activity can continue, and quality animal feed products can be used as additional income for Livestock Group Kajen District, Pekalongan Regency.